Simulasi Metode Monte Carlo dalam Menjaga Persediaan Alat Tulis Kantor - Prawita, Riska (SAFE-Network, 2021)
The use of office stationery in an educational institution is an absolute necessity. Provision of adequate and well-managed office stationery will achieve good effectiveness and efficiency as well. This study aims to predict the demand for office stationery using a Monte Carlo simulation. Monte Carlo simulation is a probabilistic method that determines odds based on random numbers. The data used in this study was the data on requests for Office Stationery in 2018 to 2019 at IAIN Batusangkar. The data was processed based on the Monte Carlo simulation stage by generating random numbers from the data. The results of the Monte Carlo simulation conducted in this study showed an accuracy rate of 96.92 % and were able to predict the demand for Office Stationery. Based on the level of accuracy generated in this study, the Monte Carlo Simulation can be used to predict the demand for Office Stationery for the following year. So, by knowing the demand for Office Stationery, the supply of Office Stationery at IAIN Batusangkar is maintained and effectiveness and efficiency are also achieved.